2019
DOI: 10.1039/c8cp06509h
|View full text |Cite
|
Sign up to set email alerts
|

From nano-emulsions to phase separation: evidence of nano-segregation in (alkane + perfluoroalkane) mixtures using 129Xe NMR Spectroscopy

Abstract: In this work we demonstrate that mixtures of (hexane + perfluorohexane) above the upper critical solution temperature segregate by forming domains at the nanometric scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Anomalies in the transport [29] and surface [30] properties of mixtures of alkanes and perfluoroalkanes have also been reported. At the molecular scale, nano-segregation has been demonstrated in (n-hexane + n-perfluorohexane) mixtures, above the upper critical solution temperature (UCST) [31][32][33]. In addition, it has been recently demonstrated that the presence of fluorinated groups induces conformational changes in hydrogenated chains, leading to more globular arrangements, increasing the proportion of gauche conformations [34].…”
Section: Introductionmentioning
confidence: 99%
“…Anomalies in the transport [29] and surface [30] properties of mixtures of alkanes and perfluoroalkanes have also been reported. At the molecular scale, nano-segregation has been demonstrated in (n-hexane + n-perfluorohexane) mixtures, above the upper critical solution temperature (UCST) [31][32][33]. In addition, it has been recently demonstrated that the presence of fluorinated groups induces conformational changes in hydrogenated chains, leading to more globular arrangements, increasing the proportion of gauche conformations [34].…”
Section: Introductionmentioning
confidence: 99%
“…Using the united atom version of the TraPPE force field, Zhang and Siepmann found that a 1% increase of the unlike segment size parameter and an 11% reduction of the unlike attractive well depth were necessary to obtain an adequate description of envelope of liquid–liquid equilibria (LLE) and the corresponding upper critical solution temperature (UCST) for the CH 4 + CF 4 mixture. Following a similar line of reasoning, in recent work we have systematically demonstrated that increasing unlike-size parameters is essential to account for the large excess volumes displayed by these systems. ,,, More than mere empirical refinement, these adjustments highlight that the peculiar properties of these systems are not only a consequence of weak relative attractive interactions, but are also related to the repulsive part of the intermolecular potential. Moreover, at the molecular level, the simulations clearly demonstrate segregation between the two mutually phobic chains.…”
Section: Introductionmentioning
confidence: 64%
“…This is commonly interpreted as an indication of weaker than anticipated unlike interactions. Anomalies in the transport and surface properties of mixtures of alkanes and perfluoroalkanes have also been reported. At the molecular scale, nanosegregation has been demonstrated in ( n -hexane + n -perfluorohexane) mixtures, above the upper critical solution temperature (UCST). The existence of spatial inhomogeneities in density and composition that gradually increase as the temperature is decreased, forming progressively larger and more stable domains that finally demix into coexisting liquid phases, has been inferred from 129 Xe NMR spectra.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main purposes of our current work is to understand how the solubility of water in mixtures of alkanes and perfluoroalkanes is affected by the large deviations from ideality. At the molecular level, nanosegregation in (n-hexane + n-perfluorohexane) mixtures, above the upper critical solution temperature (UCST), has been inferred from 129 Xe NMR spectra and confirmed by molecular-dynamics simulation [11,12]. The global reorganisation of the fluid resulting from the mixing process and, in particular, the extremely large excess volume ( ∼ 5cm 3 mol −1 [13]) can be expected to have an impact on the solubility of small solutes, such as water, in alkane + perfluoroalkane mixtures.…”
Section: Introductionmentioning
confidence: 84%